The improved “four- line model” of the organization of the risk management system in banks and banking groups of Ukraine - Chaplyha, Volodymyr (Herald of Economics, 2023)
Introduction. The deepening global economic downturn, high level of uncertainty and significant losses of Ukraine’s economy as a result of russia’s military aggression lead to restrictions on business activity and require economic agents to focus on improving the efficiency of their activities in the face of a constantly changing landscape of growing risks and limited resources. This is especially true of the banking sector, where transformation processes are ongoing, accompanied by modern external and internal challenges and threats.Purpose. The purpose of the study is to improve the model of organization of the risk management system in banks and banking groups in today’s dynamic environment with a significant level of uncertainty of transformation processes in the country’s financial sector. Methods. To achieve this goal, the research uses both general scientific methods of analysis, synthesis, analogies, and special methods of scientific knowledge, in particular, system analysis, risk management and modeling of the organization of the risk management system in a bank.Results. It is shown that the traditional model of “three lines of defense” against risks recommended for use by Ukrainian banks, as well as the updated “three lines model”, have certain drawbacks due to suboptimal distribution of information and insufficient effectiveness of risk management measures at different levels of management. The well- known model of “four lines of defense” does not take into account the specifics of the subjects of influence on risk management in the banking sector of Ukraine. An improved “four lines model” of organization of the risk management system in banks and banking groups of Ukraine is proposed, which is focused on the synergy of interaction between the subjects of influence and the use of opportunities to achieve certain goals.Perspectives. In the future, it is promising to study the use of artificial intelligence when using the proposed improved «four-line model” in risk management systems.